An Intramolecular Silylene Borane Capable of Facile Activation of Small Molecules, Including Metal‐Free Dehydrogenation of Water. (27th February 2017) - Mo, Zhenbo; Szilvási, Tibor; Zhou, Yu‐Peng; Yao, Shenglai; Driess, Matthias
Abstract: The first single‐component N‐heterocyclic silylene borane 1 (LSi‐R‐BMes2 ; L=PhC(N t Bu)2 ; R=1, 12‐xanthendiyl spacer; Mes=2, 4, 6‐Me3 C6 H2 ), acting as a frustrated Lewis pair (FLP) in small‐molecule activation, can be synthesized in 65 % yields. Its HOMO is largely localized at the silicon(II) atom and the LUMO has mainly boron 2p character. In small‐molecule activation 1 allows access to the intramolecular silanone–borane 3 featuring a Si=O→B interaction through reaction with O2, N2 O, or CO2, and formation of silanethione borane 4 from reaction with S8 . The Si II center in 1 undergoes immediate hydrogenation if exposed to H2 at 1 atm pressure in benzene, affording the silane borane 5‐H2, L(H2 )Si‐R‐BMes2 . Remarkably, no H2 activation occurs if the single silylene LSiPh and Mes3 B intermolecularly separated are exposed to dihydrogen. Unexpectedly, the pre‐organized Si–B separation in 1 enables a metal‐free dehydrogenation of H2 O to give the silanone–borane 3 as reactive intermediate. Abstract : Vereint in einer Komponente aktivieren ein N‐heterocyclisches Silylen und ein Boran eine Reihe kleiner Moleküle, darunter O2, N2 O, CO2, H2 und H2 O. Durch seine Fähigkeit zur Aktivierung von H2 O bietet sich 1 als ein metallfreies System für die Dehydrierung von H2 O an.